Reading Literacy Management in Improving Primary School Students' Learning Achievement - Linlin Nuryati; Ida Tejawiani (Journal of Science and Education (JSE), 2026)
This research is motivated by the low reading literacy in Indonesia, as evidenced by the PISA 2025 ranking that places Indonesia at 70th out of 80 countries, becoming a major challenge for the world of education. Although the government has issued various regulations such as the National Education System Law and the School Literacy Movement (GLS) to foster a reading culture, implementation in the field still faces obstacles, as indicated by fluctuations in literacy scores on the Education Report Card. This study aims to analyze reading literacy management at SDN Kemirimuka 2 and SDN Beji Timur 1. The theory of this research is to examine the management cycle according to Hanry Fayol which includes planning, organizing, directing, coordinating, and controlling. The method used in this study is a qualitative approach with a multiple case study design. Data were collected through in-depth interviews, observations, and document analysis, then analyzed using the interactive model of Miles and Huberman. The results of the study indicate that systematic and structured management of reading literacy programs based on Fayol's management principles is able to create a conducive learning environment and support a significant increase in students' reading abilities. Reading literacy management in both schools was implemented well. It has been proven that the implementation of Reading Literacy management using Henry Fayol's theory can improve the learning achievements of elementary school students.